Artificial Intelligence in the Advancement of Education in Iraq: A Theoretical Analytical Study of Systemic Readiness and Structural Constraints - Sanaa Hikmat Hasan Mahmood (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Artificial Intelligence (AI) is increasingly positioned as a transformative driver in modern education through adaptive learning, intelligent tutoring, automated assessment, and data-driven decision-making. Specific Background: Despite global advancements, AI integration in developing and post-conflict education systems such as Iraq remains constrained by infrastructural, institutional, and governance limitations. Knowledge Gap: There is a lack of a comprehensive analytical framework assessing systemic readiness and structural barriers to AI adoption within the Iraqi educational context. Aims: This study aims to examine AI applications in education, evaluate systemic readiness factors, identify implementation constraints, and propose a strategic adoption framework. Results: The analysis identifies four primary domains of AI application: personalized learning, automated assessment, teacher support, and institutional decision-making, while highlighting critical barriers including unstable electricity, limited broadband access, overcrowded classrooms, insufficient digital infrastructure, and low teacher digital competence, alongside ethical risks such as algorithmic bias and data privacy concerns. Novelty: The study offers a context-specific theoretical synthesis integrating global AI trends with Iraq’s systemic conditions through a readiness-based analytical lens. Implications: Findings suggest that sustainable AI integration requires phased implementation focusing on infrastructure development, policy alignment, teacher training, and ethical governance to support educational modernization without exacerbating inequality. Highlights:• Identifies Four Functional Domains of AI Application in National Schooling Systems• Reveals Infrastructure Instability and Skill Gaps as Primary Adoption Barriers• Proposes Phased National Strategy Integrating Policy, Capacity, and Governance Keywords: Artificial Intelligence In Education, Iraqi Education System, Digital Infrastructure, Intelligent Tutoring Systems, Educational Technology Policy.